2016
DOI: 10.1017/s0022215116009804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical intervention on middle-ear cholesteatoma with associated facial paralysis

Abstract: Early surgical treatment is more likely to give good results, and poor outcomes are observed in patients with facial nerve perineurium damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
2
6
0
3
Order By: Relevance
“…Hal ini disebabkan oleh devaskularisasi, fibrosis atau gangguan pada nervus fasialis. 12,14,15 Mekanisme terjadinya paresis nervus fasialis akibat OMSK belum dikatahui secara jelas. Namun proses inflamasi langsung yang melibatkan kanal falopi dan kompresi akibat edema dipercaya sebagai patofisiologi terjadinya paresis.…”
Section: Paresis Nervus Fasialisunclassified
See 2 more Smart Citations
“…Hal ini disebabkan oleh devaskularisasi, fibrosis atau gangguan pada nervus fasialis. 12,14,15 Mekanisme terjadinya paresis nervus fasialis akibat OMSK belum dikatahui secara jelas. Namun proses inflamasi langsung yang melibatkan kanal falopi dan kompresi akibat edema dipercaya sebagai patofisiologi terjadinya paresis.…”
Section: Paresis Nervus Fasialisunclassified
“…16 Insisi nervus hanya diperlukan pada paresis fasialis yang komplit. 15 Dekompresi saraf fasialis diperlukan pada kasus paresis komplit dengan onset akut sedangkan paresis inkomplit dengan onset akut hanya memerlukan tindakan bedah untuk eradikasi penyebab penyakit. 17 .…”
unclassified
See 1 more Smart Citation
“…Facial palsy (FP) is an uncommon but recognized complication of cholesteatoma; its incidence ranges from 1% to 3.4% of cholesteatoma presentations [ 1 , 2 , 3 ]. Facial palsy secondary to cholesteatoma has several causes; osteitis, bony erosion, direct compression resulting from edema, and inflammation of the nerve by bacteria or neurotoxic substances, which may be secreted from the cholesteatoma matrix can damage the facial nerve [ 4 , 5 ]. It has been shown that the facial nerve fills 35 to 65% of the fallopian canal; the remaining portion is filled with extra neural blood vessels and connective tissue, without leaving any empty space [ 5 , 6 ]; thus, edema secondary to infection can easily affect the neural transmission [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facial palsy secondary to cholesteatoma has several causes; osteitis, bony erosion, direct compression resulting from edema, and inflammation of the nerve by bacteria or neurotoxic substances, which may be secreted from the cholesteatoma matrix can damage the facial nerve [ 4 , 5 ]. It has been shown that the facial nerve fills 35 to 65% of the fallopian canal; the remaining portion is filled with extra neural blood vessels and connective tissue, without leaving any empty space [ 5 , 6 ]; thus, edema secondary to infection can easily affect the neural transmission [ 5 , 6 ]. Direct pressure on the facial nerve due to cholesteatoma has also been reported [ 7 ]; however, FP was expected only after blockage of more than 50% of facial nerve fibers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%